The nature of decolonisation in health sciences curricula: A scoping review - Koch, R.; Pool, J.; Heymans, Y. (South African Journal of Higher Education, 2024)
The amassed momentum from recent student protests applied pressure on Higher Education to respond to the calls for curriculum transformation. While decolonisation is viewed as an opportunity to create an inclusive and diverse learning environment, decolonising health curricula seems unachievable because the concept is not clearly defined, resulting in curricula that continue to marginalise and exclude certain groups. This scoping review explores the nature of decolonisation within Health Sciences. Online databases were used to identify 21 sources addressing the nature of decolonisation in Health Sciences. The findings indicate that decolonisation in Health Sciences is described as the process of acknowledging the impact of colonialism; combatting injustice and inequities; reclaiming and revaluing heritage; and interrogating knowledge to find alternative ways. This review added to understanding the nature of decolonisation in the Health Sciences field and its potential as a vehicle for transformation in HE (Higher Education).